A study of vibration attenuation of shear buildings under dynamic loads using TLCDs - Ghedini, Lucas Borchardt (2023)
Dissertação (mestrado) — Universidade de Brasília, Programa de Pós-Graduação em Estruturas e Construção Civil, Faculdade de Tecnologia, 2023.